Images: critical and primary sources - Manghani, Sunil (London [etc.] : Bloomsbury, 2013)
This title is a work of reference that brings together seminal writings on the image. Taking an interdisciplinary approach, the essays range across the domains of philosophy, history, art, aesthetics, literature, science, anthropology, critical theory and cultural studies. The essays reveal a wide set of perspectives, problematics and approaches, helping to frame a rich, encompassing view of what we can broadly term'image studies'. The four volumes are arranged thematically, each separately introduced and with the essays structured into specific sections for easy reference.
vol. 1. Understanding images. vol. 2. The pictural turn. vol. 3. Image theory. vol. 4. Image cultures
Keywords: Visual sociology; Visual communication; Image (Philosophy).